The Emotional Dynamics of English Language Education Students Influence the Learning Process - Zulfian Misbachul Firdaus; Yuli Mahmudah, Sentana; Ferra Dian, Andanty (Universitas PGRI Adi Buana Surabaya, 2024)
This study aims to explore professional development specifically focused on English language students in non-teaching professions. More specifically, this study examines the reasons and objectives of students choosing non-teaching professions despite majoring in English language education. This research uses qualitative case studies as its research design, in which interviews with three English language students were conducted by the researcher as a data collection technique. Personal interviews were used to obtain data. From the data collected, the results show that motivation, interest, and finances are the most obvious factors why English language students prefer non-teaching professions. Although there are many options and reasons for them to become teachers, English language students believe that they can consistently choose non-teaching professions with their English language skills. These findings explain the understanding of education students about their reasons and objectives for choosing non-teaching professions.